2019
DOI: 10.1111/1744-9987.12888
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Oral Dosing of Roxadustat in Peritoneal Dialysis Chronic Kidney Disease Patients with Anemia: A Randomized, Phase 3, Multicenter, Open‐Label Study

Abstract: Roxadustat is an oral hypoxia‐inducible factor prolyl hydroxylase inhibitor developed to treat anemia in chronic kidney disease (CKD) patients. This Phase 3, randomized, open‐label, 24‐week study investigated the efficacy and safety of roxadustat in Japanese CKD patients with anemia on peritoneal dialysis (PD) who were previously treated or not treated with erythropoiesis stimulating agents (ESAs). Patients not previously receiving ESA (ESA‐Naïve group) were randomized to roxadustat at a starting dose of 50 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
99
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 15 publications
14
99
1
3
Order By: Relevance
“…A decrease in the levels of hepcidin was also observed throughout the study. Overall, these findings confirm those of previous studies in ESA-naïve patients [17] (CL-0308) and patients converted from ESAs [17] (307 and 312) and suggest that treatment with roxadustat improves iron metabolism and mobilization.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A decrease in the levels of hepcidin was also observed throughout the study. Overall, these findings confirm those of previous studies in ESA-naïve patients [17] (CL-0308) and patients converted from ESAs [17] (307 and 312) and suggest that treatment with roxadustat improves iron metabolism and mobilization.…”
Section: Discussionsupporting
confidence: 89%
“…In line with previous studies, roxadustat was generally well tolerated in NDD-CKD patients who were ESA-naïve [14,17]. Common TEAEs were nasopharyngitis (20.2%), hypertension (6.1%), diarrhea (5.1%), and hyperkalemia (5.1%), and no deaths occurred throughout the study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar findings were also reported in two recent phase 3 studies. A Japanese study showed that in CKD patients on PD who were ESA‐naïve, roxadustat increased and maintained Hb in the target range; however, the time to reach the target was shorter (2‐4 weeks) than that observed in this study (6 weeks), possibly due to higher Hb levels at baseline 14 . Comparable results were also reported in a Chinese study in CKD patients on HD or PD 15 .…”
Section: Discussionsupporting
confidence: 50%
“…HIF-PHIs increase Hb levels by activating the body's natural response to hypoxia independent of cellular oxygen levels [5]. Roxadustat is an orally administered HIF-PHI that has shown safety and efficacy in phase 3 trials [6][7][8], and was recently approved in China for the treatment of anemia in dialysis-dependent and non-dialysis-dependent CKD patients, and in Japan for the treatment of anemia in dialysis-dependent CKD patients. Roxadustat is currently being investigated internationally in both dialysisdependent and non-dialysis-dependent patients.…”
Section: Methodsmentioning
confidence: 99%